The Psychology School Mental Health Initiative: An Innovative Approach to the Delivery of School-Based Intervention Services. (March 2013) - Millar, Golden M.; Lean, Debra; Sweet, Susan D.; Moraes, Sabrina C.; Nelson, Victoria
Evidence suggests that schools have, by default, become the primary mental health system for students in Canada. The goal of the present study was to design, implement, and evaluate the Psychology School Mental Health Initiative (PSMHI). The PSMHI is an innovative attempt to increase the capacity of school-based psychology staff to deliver evidence-based mental health intervention to children and adolescents with mental health concerns. The conceptualization, implementation, and initial outcomes of the PSMHI are outlined. Advantages and challenges of delivering cognitive–behavioural intervention in a school setting are discussed. Preliminary data indicated that participation in the initiative increased the capacity of school psychology staff in the provision of mental health service. Furthermore, results revealed that a higher number of students with mental health issues received evidence-based intervention. Finally, recommendations for enhancing effective service delivery and the expanding role of psychology with the school system are highlighted.